Kualitas Pelayanan Administrasi Kependudukan Kelurahan Penjaringansari Terhadap Kepuasan Masyarakat - Niswatin, Heni; Primandhana, Wiwin Priana (Peneliti.net, 2024)
Population administration is a right that all Indonesian citizens must have, this right does not look at age and gender. Therefore, it is important and mandatory for all Indonesian citizens to take care of population administration files from an early age, starting from birth, because these files are of course very valuable and will definitely be used in daily activities. In order to achieve population administration targets, the Surabaya City Government launched an innovation called Klampid New Generation to facilitate population administration. This innovation provides convenience for the community and service officers in the Penjaringansari District area. This article analyzes the effectiveness of population administration services through the Klampid New Generation in Penjaringansari Subdistrict in order to realize the goals of the Surabaya city government, namely ease of approach and effectiveness of population administration management. The results of the discussion showed that after the emergence of innovation accompanied by socialization, citizens' awareness increased and they were very enthusiastic about experiencing this new innovation.